Mechanical properties of gold nanowires prepared by nanoskiving approach. Issue 15 (7th April 2020) - Fang, Zhuo; Geng, Yanquan; Wang, Jiqiang; Yan, Yongda; Zhang, Guoxiong
Abstract : The mechanical properties of nanowires fabricated by nanoskiving have been studied by an AFM three-point bending test for the first time. Abstract : The nanoskiving method based on nanocutting process is a new, low cost and easy way to machine nanowires. In this study, this technique is used to machine Au nanowires with different cutting directions and depths. Young's modulus and the yield strength of nanowires are then measured by an atomic force microscope-based three-point bending test. Results show that the Young's modulus of nanowires is independent of size and is not affected by cutting directions. However, the yield strength of nanowires machined by parallel cutting (NWs-b) is 42–64% higher than that machined by perpendicular cutting (NWs-a).